Exercise Modalities for Improving Frontal Plane Knee and Foot Posture in Healthy Adults: A Systematic Review - Gülsüm Mandir Cömert; Markus Gruber (Sports)
Lower extremity misalignments increase the risk of chronic overload and acute injuries during sports and daily activities. Medial positioning of the knee and foot in the frontal plane is one of the key biomechanical risk factors associated with lower extremity injuries and pain. Different exercise interventions have been implemented to counteract misalignments. However, most studies have been conducted on clinical populations. Therefore, in this review, we aimed to assess the preventive effects of exercise interventions on frontal plane knee and foot posture in healthy individuals. Electronic databases (PubMed, Web of Science, PEDro) were systematically searched for original articles published between 2008 and 2024. This review included clinical trials on healthy adults (18–45 years) with or without lower extremity biomechanical misalignments, examining the effects of exercise interventions alone on knee and foot frontal plane biomechanics. Eligible studies reported at least one relevant frontal plane foot and knee biomechanical measure, such as knee valgus/abduction, medial knee displacement, foot pronation/eversion, or navicular drop. Studies involving non-exercise interventions, single-session protocols, and participants with neurological or spinal disorders, pain, or injury were excluded. A total of 35 articles with 1095 participants were included in this review. A total of 20 studies included individuals without a biomechanical misalignment, and 15 studies focused on individuals with a biomechanical misalignment. Mean values, standard deviations, and p-values were extracted from the included studies. Effect sizes and confidence intervals were then calculated to provide a quantitative presentation of the data. In conclusion, in healthy individuals without biomechanical misalignment, technique training and core muscles strengthening were most effective for improving knee valgus. Hip, core, and foot muscle strengthening reduced foot pronation in those with pronated feet, while short foot exercises improved foot positioning in individuals with flat feet. Combining lower extremity strengthening with knee position control training may reduce knee valgus in individuals with increased knee valgus.